The Influence Of Competence, Compensation And Job Satisfaction On Employee Work Quality In Industrial Companies Yogyakarta - Putri, Dienovita Arifka; Syamsul Hadi; Tri Ratna Purnamarini (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Employee work quality is related to the performance of an employee, performance means the result of a process measured based on agreements or SOPs that have been made by the company. This study aims to test and analyze the influence of competence, compensation and job satisfaction on employee work quality in one of the agencies engaged in the industrial sector of Yogyakarta. The population in this study were all employees in one of the industrial companies in Yogyakarta, totaling 50 people. 50 samples were collected using a survey method with a census technique. This research method is quantitative with data collection using a questionnaire. Data analysis uses Validity Test, Reliability Test, Simultaneous Test, and Determination Coefficient Test. The data analysis technique in this study uses the Classical Assumption Test. The research results show that competence and compensation have a positive and significant effect on employee work quality. However, job satisfaction has no effect on employee work quality. Keywords:Competence, Compensation, Job Satisfaction and Employee Work Quality